2022
DOI: 10.1097/aog.0000000000004931
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pessaries in the Treatment of Pelvic Organ Prolapse

Abstract: Pessaries are highly effective at improving the quality of life in women with pelvic organ prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Although the pessary is an effective treatment option for POP, it is often seen as a temporary solution whilst waiting for surgery, or as a therapeutic technique only when surgery is contraindicated. Few studies have assessed their effectiveness and satisfaction using validated questionnaires, and none have been carried out in a French population [ 4 ]. The main purpose of our study was to assess the satisfaction of patients 6 months after having been fitted with a pessary by means of a validated indicator (Patient Global Impression of Improvement, PGI-I) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the pessary is an effective treatment option for POP, it is often seen as a temporary solution whilst waiting for surgery, or as a therapeutic technique only when surgery is contraindicated. Few studies have assessed their effectiveness and satisfaction using validated questionnaires, and none have been carried out in a French population [ 4 ]. The main purpose of our study was to assess the satisfaction of patients 6 months after having been fitted with a pessary by means of a validated indicator (Patient Global Impression of Improvement, PGI-I) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…First-line treatment of pelvic organ prolapse (POP) involves the use of a vaginal pessary combined with pelvic floor exercises, whatever the patient’s age and type of prolapse [ 1 , 2 , 3 ]. A recent Cochrane meta-analysis showed that pessaries, in addition to pelvic floor muscle training, improved women’s POP symptoms and prolapse-specific quality of life [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal pessaries are an effective and safe nonsurgical treatment option for patients with symptomatic pelvic organ prolapse (POP), 1 a common and stigmatized medical condition that greatly impairs quality of life for millions of patients worldwide 2–4 . Contemporary pessaries are manufactured according to a limited set of shapes and sizes using mass production methods, 5 which may compromise their efficacy rate.…”
mentioning
confidence: 99%